Apolipoprotein E Polymorphism and Lipid Metabolism Disorders in Children with Cholelithiasis - Ye.V. Shutova (Zaslavsky O.Yu., 2016)
Relevance. The incidence of cholelithiasis in children in Ukraine has increased from 0.1-1 to 4.8 % in the structure of biliary pathology [6, 9, 13]. Rising the incidence of cholelithiasis in childhood is obvious, but the reasons are not clear. The genetic factors of this disease in childhood are underinvestigated. Objective: to study the associations of apolipoprotein (Apo) E subclasses and parameters of lipid spectrum in children with cholelithiasis. Materials and methods. 44 children (24 girls and 20 boys) with cholelithiasis aged 5-18 years were under supervision. The study involved patients with stage I (n = 23) and stage II (n = 21) cholelithiasis. Genotyping has been performed by Apo E alleles using polymerase chain reaction method (Termocycler test system). Lipid profile has been assessed in different Apo E phenotypes. The findings were statistically processed using STATISTICA 6.0 software package. Results. It has been found that low-density lipoprotein level was significantly different in E3/E4 and E4/E4 phenotypes (pk-w < 0.01). Very-low-density lipoprotein levels differed most significantly in E3/E3 and E3/E4 phenotypes (pk-w = 0.02). So, very-low-density lipoprotein values in E3/E4 phenotype were significantly higher than in E3/E3 phenotype (0.89 ± 0.12 mmol/l versus 0.36 ± 0.06 mmol/l, pu < 0.05). In patients with E4/E4 phenotype, atherogenic index was significantly higher (3.45 ±  0.34 c.u.) than in E3/E3 phenotype (2.17 ± 0.12 c.u., pu < 0.05) and E3/E4 phenotype (1.84 ± 0.24 c.u., pu < 0.05). Conclusion. Analysis of lipid spectrum in children with cholelithiasis and different Apo Е phenotypes gives an indication of genetic susceptibility to lipid metabolism disorders. Marker of increased risk for cholelithiasis development is E4/E4 phenotype.